Effects of ivermectin residues on dung invertebrate communities in a UK farmland habitat. Issue 1 (28th March 2013) - Sutton, Gemma; Bennett, James; Bateman, Mark; Stewart, Alan; Lobo, Jorge M.
Abstract Ivermectin is a broad‐spectrum antiparasitic drug, routinely administered to livestock worldwide, and concerns have been raised about its impacts on non‐target dung fauna and pasture systems. This study reports the effect of sward structure (long sward, short sward, or bare ground) on ivermectin persistence and cowpat colonisation by invertebrates, during an on‐farm experiment in the United Kingdom. The levels of ivermectin in cowpats were high [21 899 μg kg−1 (dry weight) 1 day after treatment with a pour‐on formulation] and remained detectable throughout the 47‐day trial. Residue breakdown occurred, but levels persisted above those lethal to some invertebrates. Sward structure had no significant effect on ivermectin levels. Ivermectin residues affected cowpat colonisation. Diptera were present in significantly lower numbers in treated cowpats. Coprophagous Coleoptera were less affected by ivermectin residues, although some species were present in significantly higher numbers in treated cowpats in the long sward environments. The non‐target effects of pesticides are currently of concern to policy makers. The results of this research add further weight to these concerns, particularly with regard to the duration for which ivermectin persists in situ in UK pasture, and because of the preferential attraction to treated cowpats exhibited by coprophagous Coleoptera.